2013
DOI: 10.4321/s1130-01082013000100003
|View full text |Cite
|
Sign up to set email alerts
|

Fully covered self-expanding metal stents in the management of difficult common bile duct stones

Abstract: Background and objectives: plastic biliary stents are often used after an ERCP session without complete common bile duct stones (CBDS) extraction. Sometimes, the volume of biliary drainage with these stents may be insufficient. We present our experience with the use of fully covered self-expanding metal stents (FCSEMS) in the setting of incomplete CBDS extraction.Patients and methods: after an ERCP session with difficult CBDS not completely removed, biliary FCSEMS (Wallflex) were inserted in some patients wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…In large CBD stones where extraction was not possible and plastic stent drainage was thought to be inadequate, such as in cases of distal CBD stricture, Garcia‐Cano et al . evaluated the use of fully covered self‐expanding metal biliary stents (FCSEMS) . They concluded that successful biliary drainage could be achieved in 100% of 29 cases.…”
Section: Biliary Stentingmentioning
confidence: 99%
See 1 more Smart Citation
“…In large CBD stones where extraction was not possible and plastic stent drainage was thought to be inadequate, such as in cases of distal CBD stricture, Garcia‐Cano et al . evaluated the use of fully covered self‐expanding metal biliary stents (FCSEMS) . They concluded that successful biliary drainage could be achieved in 100% of 29 cases.…”
Section: Biliary Stentingmentioning
confidence: 99%
“…[46][47][48][49] In large CBD stones where extraction was not possible and plastic stent drainage was thought to be inadequate, such as in cases of distal CBD stricture, Garcia-Cano et al evaluated the use of fully covered self-expanding metal biliary stents (FCSEMS). 50 They concluded that successful biliary drainage could be achieved in 100% of 29 cases. FCSEMS were removed after a median of 199.5 days in 16 cases (rest were deemed to unfit for repeat procedure) of which 93.7% could have a complete stone extraction.…”
Section: Biliary Stentingmentioning
confidence: 99%
“…Biliary stenting is a widely accepted rescue method in patients with failed stone extraction under endoscopic retrograde cholangiopancreatography (ERCP) and plastic biliary stents are commonly used around the world[1,2]. It is worth noting that fully covered self-expanding metal stents (FCSEMS) have been used in the management of difficult common bile duct stones (CBDS) and have gained satisfactory clinical outcome[3-7]. In the research of Garcia-Cano’s group[3], FCSEMS implantation was adopted after an ERCP session without complete CBDS extraction.…”
Section: Introductionmentioning
confidence: 99%
“…7 More recently, FCSEMSs have been reported in the management of difficult CBD stones, with success rates of 82% and adverse event rates of 17%. [8][9][10] The study by Hartery et al 1 is notable for the limited use of advanced techniques of CBD stone removal (36%), by the high rate of adverse events (15%), and by the low rate of success (82%). ML or intraductal lithotripsy may allow clearance of stones from the CBD in more than 90% of cases, with an adverse event rate of less than 10%.…”
Section: To the Editormentioning
confidence: 99%